Sage Collett: capstone - Collett, Sage, artist (Colorado State University. Libraries, 2022)
The artist's statement: A restlessness fuels my art practice. As we face challenges, experience, and learn, we constantly receive new information. It is easy to become overwhelmed, and there are too many things to say and too many things to create art about. I continuously question how art is defined in modern times. What qualifies as art? Is ‘true’ art based on skill or professionalism and experience of the artist? Or is it based on a more subjective criteria of passion, creativity, or intention behind the art? When does this categorization become too rigid and constraining? Perhaps, subconsciously, I ask these questions because of my interest in the ever-changing language of our times and my personal identity that often resists efforts to categorize and define. In terms of art making, rather than become specialized in a particular media or subject matter, I find myself inclined towards exploring various processes, being ‘inconsistent’. For the most part, I work within 2D parameters, but I often rapidly switch between media, subject matter, theme, etc., using whatever I instinctively feel will best communicate my current thoughts. Up until recently, I used these aspects rather singularly, but for this series, I thematized inconsistency itself. Rather than avoid my innate restlessness, I made it the focus and explored that process. To aid my decision making within this broad concept, I began by creating separate lists. One for traditional art styles and movements along with some personal additions. Another list for media, including charcoal, pastel, watercolor, ink, paint, etc. Finally, a list for subject matter, determining whether I would be incorporating elements of the natural world, an interior space, something more figural, or abstract. I then plugged these lists into an algorithm that would randomize my choices. Accordingly, I created works based on those randomized combinations, impulsively deciding canvas size, composition, and imagery. For some, I still produced singular pieces with two styles, one medium, and a main subject matter. As I continued within my project, I began operating in a looser manner, incorporating multiple styles and media on a single canvas, either making each section distinct or allowing the aspects to blend and interact with one another in a natural, spontaneous way. When I first planned this series, I wanted to see what would happen if I gave myself parameters – if I relinquished some of my agency – and surprisingly, in return, I received some control. Each random set of guidelines sparked an excitement, a challenge, almost like solving a puzzle. I learned how to toss aside inhibitions, and instead, work spontaneously, rapidly, allowing my intuition to guide me. The technical ‘success’ or visual unity of the series faded as a concern because this series centers around the process, finding meaning and expression within my system as it evokes questions about how we view art in modern times.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing